Use of perioperative ureteral stent in abdominal aortic aneurysm with retroperitoneal fibrosis - A report of two cases - - Kusaka, Junya (The Korean Society of Anesthesiologists, 2012)
Retroperitoneal fibrosis is associated with fibroblast proliferation due to inflammatory changes in adipose/fibrous tissue. Given that aortic dilation in abdominal aortic aneurysm can cause compression of the ureter, abdominal aortic aneurysm complicated by retroperitoneal fibrosis is likely to result in urinary tract obstruction. Accordingly, close attention to changes in perioperative urine volume is warranted when operating on patients with abdominal aortic aneurysm complicated by retroperitoneal fibrosis. We have recently performed laparotomies on two cases of abdominal aortic aneurysm complicated by retroperitoneal fibrosis. In the first case, surgery was performed without the placement of a ureteral stent. The patient developed postrenal acute renal failure caused by postoperative urinary retention. In the second case, ureteral stent placement in advance enabled perioperative management without complications. The clinical course of these cases suggests that, in laparotomy with concomitant retroperitoneal fibrosis, preoperative ureteral stent placement can prevent postoperative complications in the renal and urinary systems.